Analisis Efektifitas Machine Learning Pada Saham PT. Adaro Energy: SVM, NN, K-NN Dan RL Dengan Rapidminer - Thobibuddin, Firstiawan Fadhil; Widiantoro, Albertus Dwiyoga (Computing and Information System Journal, 2025)
This research investigates the effectiveness of four machine learning models in predicting the stock prices of PT Adaro Energy Tbk. The models evaluated include Support Vector Machine, Neural Network, K-Nearest Neighbors, and Linear Regression. Daily stock price data was collected from the period of June 3, 2019, to May 31, 2024, then processed and trained using preprocessing techniques to ensure the quality of the analyzed data. Each model was evaluated using prediction accuracy metrics and Root Mean Squared Error on a separate test dataset. The experimental results show that LR provides the best performance with the lowest RMSE value, followed by SVM, KNN, and LR. These findings indicate that LR can be an optimal choice for predicting the stock prices of PT Adaro Energy Tbk in this context.